Trend of Caesarean Section in Bheri Zonal Hospital - Thapa, Kalpana Kumari; Parajuli, Urmila (Journal of Nepalgunj Medical College, 2018)
Introduction: Caesarean Section (CS) rates are a major public health concern and cause worldwide debates according to latest data from 150 countries. Currently 18.6% of all births occur by CS, ranging from 6 to 27.2% in the least and most developed regions. This study was done to find out incidence and outcome of CS and geographical variation of women coming for the service in this Zonal Hospital.Methods: A retrospective review of case files of 771 women who had CS from 16th April 2017 to15th April 2018 were analyzed for demographic profile like age, parity, geographical location. Similarly, gestational age, various indications of CS, incidence, parity, maternal and fetal outcome and duration of hospital stay were recorded.Results: Out of 5083 deliveries, 771 (15.17%) had CS. Most of the CS was done for Cephalopevic disproportion (CPD) which was 175 (22.70%) and previous CS, 140 (18.15%). Majority of CS which was 328 (42.54%), in age group 20-24 years. In relation to parity nulliparous were 463 (60.05%). Maternal morbidity was 31 (4.02%) and maternal mortality was one after CS. Apgar score of the baby between 0-3 was 3.24%. Three babies were expired within 24 hours due to severe birth asphyxia. The patients from Banke district were 408 (52.92%).Conclusion: Study showed CS rate, 15.7% which is in upper limit of WHO recommendation and 60.50% were nulliparous had CS and most common indication of CS was CPD and fetal distress. There was no CTG used in routine practice.